The role of androgen therapy in acquired aplastic anemia and other bone marrow failure syndromes - Nassani, Momen; Fakih, Riad El; Passweg, Jakob; Cesaro, Simone; Alzahrani, Hazzaa; Alahmari, Ali; Bonfim, Carmem; Iftikhar, Raheel; Albeihany, Amal; Halkes, Constantijn; Ahmed, Syed Osman; Dufour, Carlo; et al. (Frontiers in Oncology, 2023)
Bone marrow failure syndromes are a heterogeneous group of diseases. With the major advancements in diagnostic tools and sequencing techniques, these diseases may be better classified and therapies may be further tailored. Androgens, a historic group of drugs, were found to stimulate hematopoiesis by enhancing the responsiveness of progenitors. These agents have been used for decades to treat different forms of bone marrow failure. With the availability of more effective pathways to treat BMF, androgens are less used currently. Nevertheless, this group of drugs may serve BMF patients where standard therapy is contraindicated or not available. In this article, we review the published literature addressing the use of androgens in BMF patients and we make recommendations on how to best use this class of drugs within the current therapeutic landscape.